Legal Fiction of Corporate Zakat: Ontological Paradox and Functional Hypocrisy in Islamic Financial Reporting - rhonny riansyah; Iskandar Arnel; Alchudri Alchudri; Novi Yanti; Sofiandi Sofiandi (LPPM Institut Agama Islam Diniyyah Pekanbaru, 2026)
This study aims to examine the ontological paradox and systemic inconsistency of the corporate status as a legal subject of zakat (muzakkī) in contemporary Islamic jurisprudence. Adopting a critical interpretive paradigm and abductive design, this study synthesizes Foucauldian genealogy, John Searle's